Biomimetic synthesis of fluvirosaone A - Kang, Gyumin; Han, Sunkyu (Bulletin of the Korean Chemical Society, 2024)
Over the past century, biomimetic synthesis has significantly enhanced our understanding of the biosynthetic pathways involved in the formation of natural products. In this article, we present a two‐step biomimetic synthesis of fluvirosaone A from 2,3‐dehydroallosecurinine, featuring a Nazarov‐type cyclization as the key step. Based on our synthetic results and computational analysis, we propose an alternative biosynthetic route for fluvirosaone A, identifying pyruvaldehyde as the likely source of the extraneous three carbons incorporated into the securinega skeleton. This communication presents the biomimetic synthesis of fluvirosaone A, a pentacyclic high‐oxidation state securinega alkaloid. Drawing from both experimental and computational studies, we propose a new biosynthetic pathway for fluvirosaone A, identifying pyruvaldehyde as the source of the three additional carbons integrated into the securinega framework.